Corporate governance at Martha Stewart Living Omnimedia : not "a good thing" - Shein, James B., 1942- ([London] : SAGE, 2016)
The case opens with Martha Stewart's 2005 release from prison following her conviction for obstructing an insider-trading investigation of her 2001 sale of personal stock. The scandal dealt a crippling blow to the powerful Martha Stewart brand and drove results at her namesake company, Martha Stewart Living Omnimedia (MSO), deep into the red. But as owner of more than 90 percent of MSO's voting shares, Stewart continued to control the company throughout the scandal.
Originally Published in: Shein, J. B. (2014). Corporate Governance at Martha Stewart Omnimedia: Not "A Good Thing." 5-413-761. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Martha Stewart Living Omnimedia; Corporate governance -- Case studies; Strategic planning -- Case studies